Evaluating the Interplay between Transmissibility and Virulence of SARS-CoV-2 by Mathematical Modeling - Lombardi Jr, L. P.; Yang, H.; Spira, B.; Yang, A. C. (Trends in Computational and Applied Mathematics, 2023)
During the first months of 2020 SARS-CoV-2 spread to all continents, virtually reaching all countries. In the subsequent months, new variants emerged in different regions of the world. A mathematical model based on the Covid-19 natural history encompassing the age-dependent fatality was applied to evaluate SARS-CoV-2 transmissibility and virulence. Transmissibility was assessed by calculating the basic reproduction number R0 and virulence by counting the proportion of severe Covid-19 cases and deaths. The model parameters were adjusted against the data observed in the state of São Paulo, Brazil, considering two different levels of virulence. The severe Covid-19 cases and deaths were three times higher and R0 was 25% lower when the more virulent SARS-CoV-2 variant was compared to the less virulent variant. However, under the high-virulence scenario the number of transmitting individuals is 25% lower, mainly due to the isolation of symptomatic individuals. The corollary that transmission increases in the low virulence scenario is also true. The estimated parameters, using data from São Paulo up to May 13, 2020, showed that the Covid-19 epidemic predicted with low virulence SARS-CoV-2 transmission matched the observed data just before the beginning of the relaxation, which occurred by mid-June 2020. The assessment of the interplay between transmissibility can be applied to explain in somehow the appearance of gamma and omicron variants of concern in São Paulo.